Engineering ethics - Mitcham, Carl (Prentice Hall, 2000)
An introduction to using Visual Basic for engineers. Introduces a disciplined approach to engineering analysis with a five-step problem-solving process. Includes numerous exercises and problems, such as "What if" and "Try It" features. For engineers and computer scientists interested in learning Visual BASIC.